Smart Pedestrian Crossing System in Campus with the Internet of Thing - Othman, Muhammad Jamilul Firdaus; Ismail, Nurulhuda; Tukiran, Zarina (Evolution in Electrical and Electronic Engineering, 2022)
In Malaysia, there have been few attempts to develop a pedestrian road crossing system focusing on disabled people. The objective of this project is to design a system for pedestrian crossing using the Internet of Things (IoT). It is another sort of crosswalk utilizing sensors to guard pedestrians while crossing. Therefore, a smart pedestrian crossing should be developed especially for disabled people. A pedestrian crossing, often known as a crosswalk, is an area where pedestrians can cross a road, street, or avenue. The PIR sensor will act as a motion detector to detect any motion from vehicles and pedestrians at the crossing site. The LCD and the alarm systems are capable of giving signals to both users of the crossing site. The prototype is capable of detecting the motion of both vehicles and pedestrians. The alert system is very important for the drivers as well as the pedestrians to be aware of the surrounding condition. In conclusion, the prototype of Smart Pedestrian Crossing in Campus with IoT has been successfully developed and validated. This project is proposed to provide a safe area for pedestrians, especially for disabled people to cross the road with minimal dependence on manpower.